Association of interleukin-6 methylation in leukocyte DNA with serum level and the risk of ischemic heart disease. (18th May 2016) - Yang, Qinghui; Zhao, Yushi; Zhang, Zhijie; Chen, Jianxin
Abstract: Background Interleukin-6 (IL-6), a multifunctional cytokine, plays an important role in the development of ischemic heart disease (IHD), and DNA hypomethylation of 2 CpGs, located downstream in the proximity of the IL-6 gene promoter, has been associated with risk factor for IHD. This study was to examine the association of blood leukocyte DNA methylation of the 2 CpGs in IL-6 with the risk of IHD and the serum IL-6 level.Methods IL-6 methylation levels of 582 cases and 673 controls were measured using the bisulfite pyrosequencing technology. Serum level of IL-6 was measured using enzyme-linked immunosorbent assay.Results The IL-6 methylation was significantly lower in IHD cases than in the controls, irrespective of CpG site. After multivariate adjustment, lower (< median) average IL-6 methylation was associated with an increased risk of IHD (OR 1.57, 95% CI 1.22–2.02, p  < 0.001). Average IL-6 methylation level was inversely associated with serum IL-6 level ( β  = −1.02 pg/mL per increase in IL-6 methylation, p  = 0.002) among IHD cases. This significant relationship was not observed among controls.Conclusions DNA hypomethylation of IL-6 gene measured in blood leukocytes was associated with increased risk of IHD. IL-6 demethylation may upregulate its expression, whereby exerting its risk effect on the development of IHD.